Analisis Penggunaan Media Sosial pada Perilaku Sosial Remaja Desa Sumberdadap Kecamatan Pucanglaban Kabupaten Tulungagung - Azis Imam Mustaqim; Dita Hendriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to examine the phenomenon of increasingly massive social media usage among adolescents, including those in Sumberdadap Village, Pucanglaban Subdistrict, Tulungagung Regency. On the one hand, social media offers various benefits for teenagers. However, on the other hand, unwise social media usage can potentially lead to negative impacts. Therefore, it is crucial to understand how adolescents in Sumberdadap Village utilize social media and its effects on their social behavior. This research is expected to provide a comprehensive overview of the social media usage phenomenon among adolescents and its impact on their social interaction, communication, and participation in community life. This study focuses on the following: 1) What social media platforms are used by adolescents in Sumberdadap Village, 2) How adolescents in Sumberdadap Village use social media, 3) How social media usage impacts the social behavior of adolescents in Sumberdadap Village. The research objectives are to identify: 1) The social media platforms used by adolescents in Sumberdadap Village, 2) How adolescents in Sumberdadap Village use social media, 3) The impact of social media usage on the social behavior of adolescents in Sumberdadap Village. This research employs a descriptive qualitative research method. Data is collected through interviews, observation, and documentation. Observation is conducted to gain a closer understanding of the research subjects, while interviews are used to openly explore the issues within Sumberdadap Village, Tulungagung. Documentation is utilized to gather data by examining existing documents and serves as a means to prepare data, allowing the researcher to obtain maximum information that accurately reflects the condition of the researched object. The results of this study reveal how adolescents in Sumberdadap Village utilize social media in their daily lives and its consequences. With a considerably high intensity of social media usage, adolescents generally utilize it as their primary means of online communication and a way to spend their leisure time. Consequently, social media brings both positive and negative impacts on adolescents, as their parents fear, if not balanced with guidance and supervision during their social media usage.